Technologies to Support Learning, Well-Being, and Communication - Häkkinen, Päivi (Human Technology, 2013)
The Finnish information society, including its school system, is facing many challenges at the moment. Decision makers, such as representatives of the Ministry of Education and Culture, have raised lively discussion on the basis of the recent PISA results. 1 The trend among Finnish students’ performance in the PISA study during the last decade is descendant. Altogether, the recent studies indicate particular worries related to both negative attitudes and lack of motivation towards learning among Finnish students, as these factors seem to be coupled with the performance and learning outcomes (Hautamäki, Kupiainen, Marjanen, Vainikainen, & Hotulainen, 2013; Kupari et al., 2013).